Relationship between insect herbivory and environmental variables in forests of northern Iran - GOODARZ HAJIZADEH; HAMID JALIL VAND; MOHAMMAD REZA KAVOSI; HASSAN BARIMANI VARANDI (Smujo International, 2016)
Abstract. Hajizadeh G, Jalilvand H, Kavosi MR, Varandi HB. 2016. Relationship between insect herbivory and environmental variables in forests of northern Iran. Nusantara Bioscience 8: 155-160. This research aimed to recognize the relationship between the intensity of insect herbivory and environmental variables (stand structure, and physical and chemical properties of soil and litter) in Hyrcanian forests, northern Iran. Three forest types (Pinus brutia, Parrotia persica-Carpinus betulus, and Fagus orientalis), which covered the elevational gradient of the study region, were selected. In each forest type, three random plots (20×20m) at 100m intervals were sampled. The dominant polyphagous species, Ennomos quercinaria (Hufnagel, 1767), belonging to Geometridae family was identified. The forest types experiencing the lowest and highest defoliation intensity were P. brutia (12±2.08) and F. orientalis (57.67±5.36), respectively. The intensity of insect herbivory was significantly correlated with various structural parameters [forest type, elevation, diameter at breast height (DBH), tree density, tree cutting and canopy opening (%)], physical and chemical properties of the soil [clay, pH, and potassium (K)], and litter properties [depth and total nitrogen (N)]. The study illustrates a way to monitor geometrid population dynamics across environmental gradients in terms of their population density, degree of polyphagy and distribution; such results could be useful for developing appropriate management plans for these economically important insects.